Capturing Market From the Economists - Don Slater (Journal of Economic Sociology, 2010)
The purpose of the paper is to consider the traditional object of micro-economic analysis from the approach of the “cultural” mediators – advertising agents – and to show the mistakes of traditional differentiation between economic and cultural analysis and well as reduction concepts steaming from it. At the same time the definitions of “market” and “product” will let us use the knowledge more efficiently and make it easier to understand the institutional processes of bordering between markets and products. The knowledge is got from the research of consumption and material culture. Along with the theoretical and substantial statements the paper contains the methodological thesis: ethnographical studies are of principal value not only for their obvious necessity to keep the relations with social practices but also for the basis for further theoretical development.  The given task is solved by the analysis of progress by the advertising agency of two products: oil “Johnson’s Baby” and crispy rolls «Energen»